2008
DOI: 10.1038/ejcn.2008.49
|View full text |Cite
|
Sign up to set email alerts
|

Time- and dose-dependent effect of psyllium on serum lipids in mild-to-moderate hypercholesterolemia: a meta-analysis of controlled clinical trials

Abstract: Objectives: Evidences from randomized clinical trials and meta-analysis have claimed an association between the use of soluble dietary fiber from psyllium and a cholesterol-lowering effect. However, there is still uncertainty as to the dose-response relationship and its long-term lipid-lowering efficacy. This meta-analysis was primarily conducted to address the dose-response relationship between psyllium and serum cholesterol level and time-dependent effect of psyllium in mild-to-moderate hypercholesterolemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…consumption of psyllium in conjunction with the NCEP Step 2 diet helps to maintain lower LDL-C concentrations without affecting HDL-C or TAG concentrations (7,10) . The 11 % (2 0·37 mmol/l) reduction in LDL-C concentrations observed in the present study is consistent with the results of previous psyllium trials in adults (7) , but higher than that recorded in short-term studies carried out previously in children and adolescents (9,23) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…consumption of psyllium in conjunction with the NCEP Step 2 diet helps to maintain lower LDL-C concentrations without affecting HDL-C or TAG concentrations (7,10) . The 11 % (2 0·37 mmol/l) reduction in LDL-C concentrations observed in the present study is consistent with the results of previous psyllium trials in adults (7) , but higher than that recorded in short-term studies carried out previously in children and adolescents (9,23) .…”
Section: Discussionmentioning
confidence: 99%
“…It is derived from the seed husk of Plantago ovata (11) and is considered a useful supplement to dietary therapy (National Cholesterol Education Program (NCEP) Step 1 and 2 diets) for the treatment of hypercholesterolaemic patients. Despite this, Haney et al (12) and Spence et al (13) have expressed certain doubts with regard to the dose -response relationship and long-term efficacy of the treatment.Although these positive effects have been clearly demonstrated in hypercholesterolaemic adults (7) , there are few, mostly old, published studies on the use of psyllium or other fibre mixtures in children or adolescents (9,10) and some (13,14) have reported inconclusive results.We hypothesised that psyllium supplementation exerts an additional lipid-lowering effect on serum LDL-C concentrations in dyslipidaemic paediatric subjects treated with the NCEP Step 2 diet. * Corresponding author: Professor S. A. Ribas, fax þ55 21 2587 6494, email ribasnut@yahoo.com.br…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analysis that included 21 studies by Wei et al [45] reported that the use of psyllium (3-20.4 g/day) is associated with a lowering of total cholesterol by 14.5 mg/dL and LDL-cholesterol by 10.8 mg/dL in subjects with mild-to-moderate hypercholesterolemia. Based on their findings, the authors calculated that the consumption of psyllium 5, 10, 15 g/day could result in 5.6, 9.0, and 12.5 % decreases in LDL-cholesterol, respectively.…”
Section: Soluble Dietary Fiber (Sdf)mentioning
confidence: 97%
“…In three meta-analyses, data on effects of dietary fiber intake on HDL-C were not available [9][10][11]. Seven meta-analyses reported that intake of dietary fiber is not significantly associated with changes in HDL-C. Two meta-analyses described that HDL-C was significantly reduced, but only by a small amount [12,18].…”
Section: Effects Of Dietary Fiber Intake On Hdl-cmentioning
confidence: 99%